2021
DOI: 10.46497/archrheumatol.2021.8423
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic measurement of the vascular wall thickness and intima-media thickness in patients with Behçet’s disease with symptoms or signs of vascular involvement: A cross-sectional study

Abstract: Objectives This study aims to measure and compare bilateral carotid intima-media thickness (CIMT), bilateral jugular, common femoral, and main portal vein wall thicknesses (VWTs) in Behçet’s disease (BD) patients with and without vascular involvement to obtain a cut-off value for vascular complications and determine their relationship with disease activity. Patients and methods Sixty-three BD patients (41 males, 22 females; median age: 38.0 years; min 20 - max 71 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Similar to other studies in which the VWT was measured in BD ( Supplementary Table S1 ), we found that the VWT of the CFV was significantly higher in the BD group than in the other study groups. While the WWT of the mean right CFV of BD patients in the present study was 0.68 ± 0.12 mm, it was found to be between 0.68–0.92 mm in other studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the present study, the WWT of the CFV had an advantage in 79.8% sensitivity and 64.7% specificity at a cutoff value of 0.58 mm.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Similar to other studies in which the VWT was measured in BD ( Supplementary Table S1 ), we found that the VWT of the CFV was significantly higher in the BD group than in the other study groups. While the WWT of the mean right CFV of BD patients in the present study was 0.68 ± 0.12 mm, it was found to be between 0.68–0.92 mm in other studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In the present study, the WWT of the CFV had an advantage in 79.8% sensitivity and 64.7% specificity at a cutoff value of 0.58 mm.…”
Section: Discussioncontrasting
confidence: 77%
“…The first controlled Doppler US study by Alibaz-Oner et al showed that vein wall thickness (VWT) increased in the lower extremity veins of male patients with BD, which was independent of vascular involvement [12]. Furthermore, other US studies involving different disease groups supported that the VWT increased in cases of BD [11,[13][14][15][16][17]. Based on these findings, it has been suggested that the measurement of the common femoral vein (CFV) thickness can be a valuable, practical, and cost-effective diagnostic tool for diagnosing BD [9].…”
Section: Introductionmentioning
confidence: 98%
“…Behçet’s disease sets itself apart from other vasculitides with an increased vein wall thickness, as evidenced by Doppler ultrasonography studies. [ 6 , 7 ] The co-occurrence of various arterial and venous events within the same patient, referred to as a vascular cluster, is a recognized phenomenon. The occurrence of venous thrombus in the majority of patients with either vascular cluster or pulmonary involvement suggests that there could be a common etiology of vascular events (thrombus, stenosis, aneurysm).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical significance is unclear since no diseased controls were included and the data is based on diagnosis codes, carrying the risk of misdiagnosis. Growing evidence indicates that venous wall thickness (VWT) of the lower extremity veins is increased in BS compared to that found in several inflammatory diseases and healthy controls (66)(67)(68)(69)(70)(71). VWT was especially increased among those BS patients with no apparent vascular involvement suggesting that VWT could be an early indication of vascular inflammation (66,71).…”
Section: Vascular Involvementmentioning
confidence: 99%